The Subaxial Cervical AO Spine Injury Score. Issue 6 (July 2022) - Canseco, Jose A.; Schroeder, Gregory D.; Paziuk, Taylor M.; Karamian, Brian A.; Kandziora, Frank; Vialle, Emiliano N.; Oner, F. Cumhur; Schnake, Klaus J.; Dvorak, Marcel F.; Chapman, Jens R.; Benneker, Lorin M.; Rajasekaran, Shanmuganathan; et al.
Study Design: Global cross-sectional survey. Objective: To develop an injury score for the AO Spine Subaxial Cervical Spine Injury Classification System. Methods: Respondents numerically graded each variable within the classification system for severity. Based on the results, and with input from the AO Spine Trauma Knowledge Forum, the Subaxial Cervical AO Spine Injury Score was developed. Results: An A0 injury was assigned an injury score of 0, A1 a score of 1, and A2 a score of 2. Given the significant increase in severity, A3 was given a score of 4. Based on equal severity assessment, A4 and B1 were both assigned a score of 5. B2 and B3 injuries were assigned a score of 6. Unstable C-type injuries were given a score of 7. Stable F1 injuries were assigned a score of 2, with a 2-point increase for F2 injuries. Likewise, F3 injuries received a score of 5, whereas more unstable F4 injuries a score of 7. Neurologic status severity rating scores increased stepwise, with scores of 0 for N0, 1 for N1, and 2 for N2. Consistent with the Thoracolumbar AO Spine Injury Score, N3 (incomplete) and N4 (complete) injuries were given a score of 4. Finally, case-specific modifiers M1 (PLC injury) received a score of 1, while M2 (critical disc herniation) and M3 (spine stiffening disease) received a score of 4. Conclusions: The Subaxial Cervical AO Spine Injury Score is an easy-to-use metric that can help develop a surgical algorithm to supplement the AO Spine Subaxial Cervical Spine Injury Classification System.